The Difference In Qirâ'ât Al-Qur'an Is Seen From The Rules Of Arabic According To Abduh Al-Rajihi In The Book Al-Lahjât Al-'Arabiyyah Fi Al-Qirâ'ât Al-Qur'âniyyah - Ekawati, Ekawati; Ivada, Putra Dian Kharisma (International Journal Labs, 2023)
The aim of this research is to analyze and describe analitically the difference in